2008
DOI: 10.1177/0959683608095581
|View full text |Cite
|
Sign up to set email alerts
|

Native Americans as active and passive promoters of mast and fruit trees in the eastern USA

Abstract: We reviewed literature in the fields of anthropology, archaeology, ethnobotany, palynology and ecology to try to determine the impacts of Native Americans as active and passive promoters of mast (nuts and acorns) and fruit trees prior to European settlement. Mast was a critical resource for carbohydrates and fat calories and at least 30 tree species and genera were used in the diet of Native Americans, the most important being oak ( Quercus), hickory ( Carya) and chestnut ( Castanea), which dominated much of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
149
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(152 citation statements)
references
References 105 publications
(35 reference statements)
1
149
2
Order By: Relevance
“…Nevertheless, the abrupt appearance at 4000 yr BP of regular fires and the marked increase in the summed relative probability of charcoal ages at 1000 years are consistent with historical trends in human activity and fire frequency hypothesized for the southern Appalachians by Delcourt (1986, 1998). Abrams and Nowacki (2008) argue that Native American use of fire to manipulate vegetation in the eastern United States was ubiquitous, driving the composition of plant communities at the regional and biome scales. The palynological record from Horse Cove Bog, North Carolina (located ;20 km from our study area), shows that chestnut, oak, and pine were prevalent in the area surrounding the bog from 4000 yr BP to the present (Delcourt and Delcourt 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the abrupt appearance at 4000 yr BP of regular fires and the marked increase in the summed relative probability of charcoal ages at 1000 years are consistent with historical trends in human activity and fire frequency hypothesized for the southern Appalachians by Delcourt (1986, 1998). Abrams and Nowacki (2008) argue that Native American use of fire to manipulate vegetation in the eastern United States was ubiquitous, driving the composition of plant communities at the regional and biome scales. The palynological record from Horse Cove Bog, North Carolina (located ;20 km from our study area), shows that chestnut, oak, and pine were prevalent in the area surrounding the bog from 4000 yr BP to the present (Delcourt and Delcourt 1997).…”
Section: Discussionmentioning
confidence: 99%
“…An analogous situation may exist in some areas of eastern North America where pre-European settlement forest composition may bear the legacy of long-term active forest management by Native Americans. Abrams and Nowacki (2008) concluded that Native Americans managed the vast majority of vegetation in the eastern United States directly or indirectly using fire as a management tool. Moreover they posited that Native Americans directly promoted mast (nuts and acorns) and fruit trees by cultivation and planting them in the eastern forests (Abrams and Nowacki 2008 and references therein).…”
Section: Palynologymentioning
confidence: 98%
“…S. Geological Survey, 1100 N. Mineral Springs Rd, Porter, IN 46304, USA e-mail: npavlovic@usgs.gov resulting in compositional and structural changes (Abrams and Nowacki 2008;Nuzzo 1986;Wolf 2004). Most prescribed burns occur in the late fall (November-December) or late winter seasons (March-April) (Howe 1994a, b).…”
Section: Introductionmentioning
confidence: 98%